SYMBOLS OF WILD ANIMALS IN THE UZBEK LANGUAGE: A MIRROR OF NATIONAL CULTURE (Ustozlar uchun, 2026)
This article explores the symbolic meanings of wild animals in the Uzbek language and their reflection of national cultural values. Through analysis of phraseological units, proverbs, epic literature, and folklore, the study examines how animals such as the wolf, fox, eagle, leopard, and snake function as cultural symbols in the Uzbek tradition and what aspects of the national worldview and mentality they reveal.